2010
DOI: 10.1038/pj.2009.338
|View full text |Cite
|
Sign up to set email alerts
|

Addition effects of imidazolium salts on mesophase structure and optical properties of concentrated hydroxypropyl cellulose aqueous solutions

Abstract: Addition effects of N-alkyl-substituted methylimidazolium salts ([CnMim][X]) on the mesophase structure and lower critical solution temperature (LCST)-type phase-separation behavior of concentrated hydroxypropyl cellulose (HPC) aqueous solutions were investigated mainly by spectrophotometry. In the cholesteric mesophase formation, at concentrations of more than 50 wt% HPC, helical pitch (P) was confirmed to shift upward according to the chaotropic strength of X -, for example, in a manner satisfying the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…6b) [31]. In the isotropic region, the surfactant-like action of the organo-cations on HPC molecules works as a T c -elevating factor, because of the gain in electrostatic stability of the solute polymer.…”
Section: Hpc-core Mesomorphic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…6b) [31]. In the isotropic region, the surfactant-like action of the organo-cations on HPC molecules works as a T c -elevating factor, because of the gain in electrostatic stability of the solute polymer.…”
Section: Hpc-core Mesomorphic Systemsmentioning
confidence: 99%
“…5a, b) are employed as additives in aqueous HPC lyotropics, particular attention should be paid to the amphiphilic structure and possible surfactant-like action of the organo-cation moiety CnMim + [31]. In mesophase formation at !50 wt% HPC, the helicoidal pitch P shifts upward according to the chaotropic strength of X À of the added IL (e.g., in a manner satisfying the order Cl À < Br À < NO 3 À < I À ) if the salt is well dissociated.…”
Section: Hpc-core Mesomorphic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in detail in previous studies, 9−12 the cholesteric periodicity and LCST-type phase boundary, and ensuing optical properties of the lyotropic system of HPC/water, are significantly affected by the addition of a small amount of inorganic salts 9 or organo-ionic liquids such as imidazolium salts 12 as the third component. As a universal rule, it was shown that both the cholesteric pitch (P) and the phase-separation temperature, and accordingly the wavelength of selective light reflection (λ M ) and the cloud point (T c ), varied systematically with a change in strength of a so-called "chaotropic" effect of the ions constituting the additive salts.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Since then, the LC behaviors of cellulose derivatives have aroused much interest in LC polymers within the scientific community. [35][36][37][38][39][40][41][42][43][44] During the past few years, rigid mesogens have been introduced into the backbone of cellulose to investigate the LC behavior of the resultant cellulose derivatives. [45][46][47][48][49] Although the chemical structure of these cellulose derivatives is similar to that of the combined MCSCLCPs, 16,26 rigid mesogenic side groups cannot form ordered structures themselves and merely function as substitutes of cellulose derivatives; therefore, these polymers exhibit the LC behavior only of the cellulose backbone.…”
Section: Introductionmentioning
confidence: 99%